Waste management practices and government-led initiatives: assessment of knowledge, attitude and practice (KAP) level in a non-urban area / Siti Yasmin Badrum and Mohammad Tahir Mapa - Badrum, Siti Yasmin; Mapa, Mohammad Tahir (Universiti Teknologi MARA, Sabah, 2021)
Malaysians are generally knowledgeable and aware of waste but have not transformed this into favorable attitudes and behaviors toward sustainable waste management practices. Regulations, economic incentives and education are just a few of the tools available to policymakers to influence behavior, particularly in non-urban areas. An assessment of the knowledge, attitude and practice (KAP) were conducted in Penampang, Sabah. A total of 401 individuals from several villages participated and responded to the KAP questionnaire. The KAP variables were assigned with scores to determine the level (weak, low, moderate and high). Pearson's correlation coefficient was employed to determine the association between knowledge, attitude and practice. Most respondents were found to have high knowledge and attitude levels but lack in practice. Knowledge and attitude were found to be significantly correlated (r = .406, p = .000). Significant negative correlation was found between knowledge and practice (r = -.139, p = .005) and attitude and practice (r = -.284, p = 000). Appropriate intervention initiatives must be enforced soon to teach environmentally friendly behaviors’ so that Malaysians can keep up with the challenges of a developed country.